DETERMINANT OF HEALTH IN SCHOOL CHILDREN WITH SCHOOL-BASED INTERVENTION: REVIEW ARTICLE - Triwahyuningsih, S.ST.,M.Kes, Ria Yulianti; Nugraheni, Sri Achadi (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Schools have an important role in health promotion especially by increasing students' knowledge, behavior and academic achievements(1). School-based health promotion can be very valuable in developing and developed countries that face the challenges of low health information technology and disease infections(2,3), published literature focuses on school-based interventions for health promotion and impact on a country(2). The author included 50 studies that met specific criteria: (i) studies especially school children or targeted adolescents; (ii) designs that are randomly received in controlled trials, controlled studies before or after the time series is interrupted; (iii) the study covers at least one measure of impact and (iv) is the main study or systematic review and observation(4). The authors found that school-based interventions can be classified into two main categories: interventions that target individual health determinants such as health knowledge, skills and behavior(5)and they target environmental determinants such as the social and physical environment at the school, family and community level(6). The findings indicate that a comprehensive approach that addresses individual and environmental determinants can lead to long-term behavioral changes and significantly improve health and education outcomes from interventions related to information technology in cellular media or social media applications(7). We highlight the need for further studies on the long-term effects of school-based interventions on health outcomes in a country.